Learning communities: schools, parents and challenges for wider community involvement in schools - Mayo, Peter (International Journal about Parents in Education, 2023)
This presentation will focus, for the most part, on a project of parental involvement in a state primary school located in a predominantly working-class area in a Mediterranean country. It will draw briefly on qualitative empirical work carried out with a colleague (Carmel Borg). The presentation gives an account of the socio-economic context of the school, and foregrounds, through empirical data culled from transcribed semi-structured interviews, the voices of parents, administrators, school-council members and teachers. It will be argued that, if this project is to develop into a genuine exercise in democratic participation, parents must begin to be conceived of not as “adjuncts”, but “subjects”. The parents interviewed in this empirical work see themselves as such, and derive confidence from the fact that, at the time of the interview, their claims and recommendations were translating into concrete developments. The second part of the presentation will discuss the issue of parental involvement in schools within the context of a wider discussion on ‘changing the face of the school’ by helping it develop into a community learning centre. Insights from the work of Paulo Freire and his Education Secretariat, when he served as Education Secretary in the Municipal Government of São Paulo, Brazil, and from SMED in Porto Alegre, Brazil, will be drawn upon.